TERP: A Trusted and Energy Efficient Routing Protocol for Wireless Sensor Networks (WSNs) - Almasri, Marwah; Elleithy, Khaled; Bushang, Anas; Alshinina, Remah (2013 IEEE/ACM 17th International Symposium on Distributed Simulation and Real Time Applications, 2013)
Recently, Wireless Sensor Networks (WSNs) have emerged to provide a variety of important applications with low cost sensors. The task of the sensors is to collect data and send it to the sink node which delivers the data to a task manager. However, these sensors have limited power and thus limited lifetime. Another important consideration in WSNs is the level of security. Transmitting data from node to another can risk the security of the data. In this paper, we propose a novel trusted and energy efficient routing protocol (TERP) based on the Destination Sequenced Distance Vector Protocol (DSDV). TERP helps to increase the security level in the network and thus avoid any malicious nodes or untrusted nodes. It also reduces the power consumption by using the trust factor. The higher the degree of trust, the less encryption is used which results in less energy. Other factors such as drop ratio, delivery ratio, average delay, and delay jitter are analyzed along a comparison of DSDV protocol with the proposed TERP routing protocol.